Politics, Government Size, and Fiscal Adjustment in Industrial Countries - Annett, Anthony (IMF Working Papers; Working Paper ;, 2002)
It is now well established that political and institutional factors matter for fiscal outcomes. Following a review of the literature, this paper examines the relationship between a variety of political-institutional variables and fiscal aggregates-encompassing the overall balance as well as expenditure and revenue and their various components-across 19 industrial countries over the past two decades. It finds strong effects on fiscal policy from such factors as type of electoral system, degree of legislative or government fragmentation, and stability of government. Some of the strongest results emerge for certain components of expenditure, such as transfers, and for the balance between labor and consumption taxation. There are clear relationships between the type of political system and choice of tax and expenditure system. The paper also examines fiscal adjustment since the late 1980s in light of these political factors, finding some evidence of a reversal in trend, but only when growth has been high or when debt has become problematic.